2006
DOI: 10.1002/adma.200600838
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible, Hydrophilic, Supramolecular Carbon Nanoparticles for Cell Delivery

Abstract: Carbon nanomaterials have received recent attention as biomolecular carriers, [1][2][3][4][5] capable of transporting covalently bonded drugs or molecular probes across cell membranes.The poor cellular penetration of many small molecules and proteins can be overcome by conjugation to a nanomaterial carrier, whose size, shape, and surface chemistry can be engineered for optimal cellular uptake. The seminal work cited above [1,2] focused on carbon nanotubes but we believe that spherical carbon nanoparticles may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 38 publications
2
79
0
Order By: Relevance
“…In the MTT assay (Figure 4(a)), increase in the concentration of untreated particles showed decreases in cell viability after 24-h incubation. Cell viabilities of cells with untreated CC particles were lower than those of cells with untreated CB, implying that CB is more biocompatible; this result is consistent with the reported cytotoxicities observed in previous studies (Yan et al 2006;Horie et al 2014). Even though slight differences are confirmed between the CB and CC particles, the labeling did not significantly alter the effect of original particles on the viability of A549 cells.…”
Section: Biological Assayssupporting
confidence: 90%
“…In the MTT assay (Figure 4(a)), increase in the concentration of untreated particles showed decreases in cell viability after 24-h incubation. Cell viabilities of cells with untreated CC particles were lower than those of cells with untreated CB, implying that CB is more biocompatible; this result is consistent with the reported cytotoxicities observed in previous studies (Yan et al 2006;Horie et al 2014). Even though slight differences are confirmed between the CB and CC particles, the labeling did not significantly alter the effect of original particles on the viability of A549 cells.…”
Section: Biological Assayssupporting
confidence: 90%
“…Thus, fullerenes, which can intercept ROS, may be extremely useful in biomedicine as cancer therapies as well as agents for helping to maintain general health. In recent studies, researchers found that Gd@C 82 (OH) 22 nanoparticles showed antineoplastic activity; these structures exhibited high efficiency and low toxicity (described in the next section).…”
Section: Ros-scavenging Property Of Fullerenesmentioning
confidence: 98%
“…For each system, the cell viability was evaluated and the intracellular ROS level was determined. It is concluded that the Gd@C 82 (OH) 22 nanoparticles exhibited the greatest cellular protective effects against hydrogen peroxide-induced cytotoxicity, followed by the fullerenol nanoparticles; the carboxyfullerene nanoparticles provided the least protection.…”
Section: Ros-scavenging Property Of Fullerenesmentioning
confidence: 98%
See 2 more Smart Citations